2015
DOI: 10.1007/s11255-015-0976-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed contrast-enhanced MRI to localize Botox after cystoscopic intravesical injection

Abstract: Diffusion of BoNT after intravesical injection is very common once bladder wall is breeched. Precise injection localization into muscle layer may not be as relevant to outcome as previously assumed. The assumption in our study that localization and diffusion of contrast also represents the localization of BoNT is open to critique as BoNT diffusion is potentially slower (Mehnert et al. in World J Urol 27(3):397-403, 2009). The absence of systemic symptoms after the injection in our series supports guidelines co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…T1 measurements resolve well the different layers of the bladder wall because of the signal-to-noise ratio is higher than with T2 measurements. 14 Post-contrast bladder wall T1 values of HL BPS/IC women were reduced from pre-contrast values by 44% compared to 18% for controls and non-HL BPS/IC patients, P < .0001. BPS/IC patients with HL had more gadobutrol diffusion into bladder wall compared to non-HL IC patients ( Figure 1).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 79%
See 1 more Smart Citation
“…T1 measurements resolve well the different layers of the bladder wall because of the signal-to-noise ratio is higher than with T2 measurements. 14 Post-contrast bladder wall T1 values of HL BPS/IC women were reduced from pre-contrast values by 44% compared to 18% for controls and non-HL BPS/IC patients, P < .0001. BPS/IC patients with HL had more gadobutrol diffusion into bladder wall compared to non-HL IC patients ( Figure 1).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 79%
“…Quantitative T1 measurements were calculated by taking differences in signal intensity of 20 pixels in pre‐contrast and post‐contrast images of bladder wall. T1 measurements resolve well the different layers of the bladder wall because of the signal‐to‐noise ratio is higher than with T2 measurements …”
Section: Diagnosticsmentioning
confidence: 99%
“…37 There is a recent application that used CE-MRI to examine the distribution of Botox (botulinum toxin) with Gd-DTPA within the bladder wall after intravesical injection directly in the wall. 38 Recently we used CE-MRI to detect alterations in bladder permeability in rat bladders exposed to protamine sulfate, and also detect an increased MRI SI within the colon due to the bladder-colon crosstalk. 9 None of these studies, however, have assessed bladder crosstalk associated with colon diseases, nor has MRI been used to assess changes in permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging represents a powerful non-invasive tool to track the spread of paramagnetic substances; however, onaBoNT-A is not paramagnetic and its spread cannot be directly detected by MRI. Several studies have reported mixing onaBoNT-A with gadolinium based contrast agents of different polarity, osmolarity, and chemical structure 25, 26 .…”
Section: Clinical Efficacy Of Intradetrusor Injectionmentioning
confidence: 99%
“…Alsinnawi et al injected onaBoNT-A with a macrocyclic uncharged gadolinium chelate 25 . OnaBoNT-A dosed at either 100U or 200U was reconstituted with 19 mL of 0.9% saline and 1 mL of Gadovist into either idiopathic overactive bladders or neurogenic bladders, respectively.…”
Section: Clinical Efficacy Of Intradetrusor Injectionmentioning
confidence: 99%